2016
DOI: 10.1021/acschembio.6b00265
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Core β-1,2-Xylosylation on Glycoprotein Recognition by Murine C-type Lectin Receptors and Its Impact on Dendritic Cell Targeting

Abstract: Targeting antigens to dendritic cell subsets is a promising strategy to enhance the efficacy of vaccines. C-type lectin receptors (CLRs) expressed by dendritic cells are particularly attractive candidates since CLR engagement may promote cell uptake and may further stimulate antigen presentation and subsequent T cell activation. While most previous approaches have involved antibody-mediated CLR-targeting, glycan-based CLR targeting has become more and more attractive in recent years. In the present study, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Since an efficient inhibition of virus/CLR interactions by glycan-based carrier systems requires a high binding avidity, multivalent ligand display using different scaffolds has been employed, including nanoparticles, dendrimers, polymers, fullerenes, and glycan-modified antigens [135,136,137,138,139,140]. Besides the inhibition of viral entry into host cells, multivalent CLR targeting also represents a promising strategy to stimulate APC effector functions to boost immune responses [141,142,143]. …”
Section: Multivalent Glycoconjugates As Antiviralsmentioning
confidence: 99%
“…Since an efficient inhibition of virus/CLR interactions by glycan-based carrier systems requires a high binding avidity, multivalent ligand display using different scaffolds has been employed, including nanoparticles, dendrimers, polymers, fullerenes, and glycan-modified antigens [135,136,137,138,139,140]. Besides the inhibition of viral entry into host cells, multivalent CLR targeting also represents a promising strategy to stimulate APC effector functions to boost immune responses [141,142,143]. …”
Section: Multivalent Glycoconjugates As Antiviralsmentioning
confidence: 99%
“…The latter one seems to be activated via the lectin pathway by the mannose binding lectins, MASP1 and MASP2. The role of C-type lectin receptors in activation of murine DC by stimulation with core β1,2-xylosylated glycoprotein was investigated by Brzezicka et al [ 34 ]. They report enhanced uptake, presentation and subsequent T-cell activation by artificially glycosylated ovalbumin; however, xylosylated glycans did not significantly enhance the activation potential in this experimental setup.…”
Section: Resultsmentioning
confidence: 99%
“…Immunization studies in mice revealed augmented antibody responses against C. albicans β-mannan. Rational design of glycan ligands of CLRs as well as the optimization of the respective protein or peptide antigen can further increase targeting efficacy [82,83]. A particularly attractive strategy is targeting multiple CLRs simultaneously to enhance targeting or to induce synergistic responses through cross-talk.…”
Section: Carrier Systems For Multivalent Display Of Glycans For Clr Tmentioning
confidence: 99%